2002
DOI: 10.1046/j.1365-2656.2002.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Search paths of swans foraging on spatially autocorrelated tubers

Abstract: Summary1. Tundra swans forage on below-ground pondweed tubers that are heterogeneously distributed in space. The swans have no visual cues to delineate patches. It was tested whether swans employ an area-restricted search tactic. Theory predicts that swans should alternate between an intensive (low-speed, sinuous) search mode in high tuber density areas and an extensive (high-speed, directed) search mode between these areas. 2. A quantitative analysis of movement paths recorded over short time frames (15 min) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 42 publications
7
88
0
Order By: Relevance
“…Resource availability at the neighbourhood spatial-scale was a consistently better predictor of lizard space use than at the local scale, implying spatial decisions are influenced by a larger scale than our single quadrats. This finding is consistent with scale-dependent foraging, where movements of animals that use patchy or spatially autocorrelated resources match intermediate spatial scales [52][53][54]. Lizards may obtain relevant information on resource distributions through direct detection [46] or through familiarity with their multi-year stable HR [34,55].…”
Section: Discussionsupporting
confidence: 78%
“…Resource availability at the neighbourhood spatial-scale was a consistently better predictor of lizard space use than at the local scale, implying spatial decisions are influenced by a larger scale than our single quadrats. This finding is consistent with scale-dependent foraging, where movements of animals that use patchy or spatially autocorrelated resources match intermediate spatial scales [52][53][54]. Lizards may obtain relevant information on resource distributions through direct detection [46] or through familiarity with their multi-year stable HR [34,55].…”
Section: Discussionsupporting
confidence: 78%
“…Navigational information can be goal-and/or sensory-system-specific. Flying swans, for example, use visual cues to detect a lake, kilometers away, but use tactile cues to detect tubers in the mud, millimeters away (31).…”
Section: Figmentioning
confidence: 99%
“…Indeed, observations at emperor penguin colonies have shown that foraging trips vary in duration as the breeding season goes on (Kirkwood and Robertson 1997a), with the suggestion being that this is brought about by changes in the environment. The complexity of environmental conditions, both biotic and abiotic, with which emperor penguins have to contend ultimately distil out into two major behavioural patterns which are expressed during foraging: (1) travelling behaviour, where birds move quickly and directly through regions inappropriate for foraging, and (2) searching behaviour, where a reduced rate of overall travel results from greater track tortuosity in regions where prey is most likely to be located (Wilson 1995;Leopold et al 1996;Jaquet and Whitehead 1999;Nolet and Mooij 2002;Wilson 2002;Markman et al 2004;Austin et al 2006). The time allocated to each of these two behaviours results in a total foraging trip duration, which modulates the rate at which chicks can acquire food and thus grow appropriately.…”
Section: Introductionmentioning
confidence: 99%